2017
DOI: 10.1080/15592324.2017.1396404
|View full text |Cite
|
Sign up to set email alerts
|

Rice ERECT LEAF 1 acts in an alternative brassinosteroid signaling pathway independent of the receptor kinase OsBRI1

Abstract: ERECT LEAF 1 (ELF1) was previously identified as a component of brassinosteroid signaling in rice. A double mutant obtained by crossing elf1-1 (a null mutant of ELF1) with d61-1 (a leaky mutant of OsBRI1) showed a more severe phenotype than did the elf1-1 single mutant, resembling that of a severe brassinosteroid-deficient mutant. Microarray analysis showed that the gene expression profile of elf1-1 was distinct from that of d61-12 (a leaky mutant of OsBRI1 with a phenotype similar to that of elf1-1), and fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previously, we reported that ELF1 is probably involved in the brassinosteroid-mediated suppression of jasmonic acid response in rice, because ELF1 suppresses stress-induced signaling and jasmonic acid signaling is stimulated in elf1-1. 24 In this study, we identified OsWRKY4 as a candidate target protein of ELF1 by yeast two-hybrid screening. ELF1 interacted with OsWRKY4 through the ARM repeats and ubiquitinated it in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that ELF1 is probably involved in the brassinosteroid-mediated suppression of jasmonic acid response in rice, because ELF1 suppresses stress-induced signaling and jasmonic acid signaling is stimulated in elf1-1. 24 In this study, we identified OsWRKY4 as a candidate target protein of ELF1 by yeast two-hybrid screening. ELF1 interacted with OsWRKY4 through the ARM repeats and ubiquitinated it in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…23 However, elf1-1 is not epistatic to the rice brassinosteroid receptor mutant d61, the gene expression profile of elf1-1 is distinct from that of d61 (as revealed by microarray analysis), and some stress response-related genes induced by jasmonic acid treatment are differentially regulated between elf1-1 and d61. 24 These findings imply that ELF1 suppresses stress-induced signaling and that jasmonic acid signaling is stimulated in elf1-1.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation